2014
DOI: 10.1073/pnas.1404829111
|View full text |Cite
|
Sign up to set email alerts
|

The B2 flowering time locus of beet encodes a zinc finger transcription factor

Abstract: Sugar beet (Beta vulgaris) is a biennial root crop that grows vegetatively in the first year and starts shoot elongation (bolting) and flowering after exposure to cold temperatures over winter. Early bolting before winter is controlled by the dominant allele of the B locus. Recently, the BOLTING TIME CONTROL 1 (BTC1) gene has been cloned from this locus. BTC1 promotes early bolting through repression of the downstream bolting repressor B. vulgaris FLOWERING LOCUS T1 (BvFT1) and activation of the downstream flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 32 publications
(34 reference statements)
3
78
1
3
Order By: Relevance
“…Previously, BBX19 was reported to be a circadian-regulated gene with a function in the output pathway downstream of the clock (Kumagai et al, 2008;Dally et al, 2014). Our data corroborate the circadian regulation of BBX19 and further demonstrate its antiphasic circadian rhythm compared with those of FT and CO.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previously, BBX19 was reported to be a circadian-regulated gene with a function in the output pathway downstream of the clock (Kumagai et al, 2008;Dally et al, 2014). Our data corroborate the circadian regulation of BBX19 and further demonstrate its antiphasic circadian rhythm compared with those of FT and CO.…”
Section: Discussionsupporting
confidence: 87%
“…This suggests that BBX19 functions as a checkpoint to prevent the expression of FT soon after the onset of CO expression and the light-induced stabilization of its protein necessary for binding to the FT promoter. Intriguingly, the B2 flowering time locus of the biennial root crop sugar beet (Beta vulgaris) was recently identified as Bv-BBX19, a close homolog of Arabidopsis BBX19 (Dally et al, 2014). The authors reported that induced mutations within the second B-box of Bv-BBX19 caused the upregulation of FLOWERING LOCUS1 (Bv-FT1), and they further proposed a model of action by which Bv-BBX19 and BOLTING TIME CONTROL1 (BTC1) complement each other and thereby acquire a CO function to regulate the downstream Bv-FT1 and Bv-FT2 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Recessive alleles of another bolting locus, called B2, confer a biennial behavior to plants homozygous for the annual allele BTC1 (Büttner et al, 2010). This locus encodes the DOUBLE B-BOX TYPE ZINC FINGER protein BvBBX19, which is orthologous to an Arabidopsis protein that negatively influences the induction of FT (Dally et al, 2014;Wang et al, 2014). Interestingly, the expression of both BvBBX19 and BvBTC1 is diurnally regulated (Pin et al, 2012;Dally et al, 2014), and although the functional relationship between these two proteins is still unclear, they both participate in the regulation of an antagonistic pair of FT-like proteins, BvFT1 and BvFT2 ( Fig.…”
Section: Vernalization Systems In Other Eudicotsmentioning
confidence: 99%
“…Interestingly, the expression of both BvBBX19 and BvBTC1 is diurnally regulated (Pin et al, 2012;Dally et al, 2014), and although the functional relationship between these two proteins is still unclear, they both participate in the regulation of an antagonistic pair of FT-like proteins, BvFT1 and BvFT2 ( Fig. 1D; Pin et al, 2010Pin et al, , 2012Dally et al, 2014). The short-day-expressed BvFT1 represses floral transition and negatively influences BvFT2 levels, whose expression is promoted by long days (Pin et al, 2010).…”
Section: Vernalization Systems In Other Eudicotsmentioning
confidence: 99%
“…Sugar beet (Beta vulgaris L.) is a biennial root crop that requires vernalisation to initiate the transition from vegetative to reproductive growth. Sugar beet is a member of the Amaranthaceae family that evolved from the monocot-dicot split~140 million years ago (Dally et al 2014). Two FLOWERING LOCUS T (FT) genes such as BvFT1 and BvFT2 of B. vulgaris had evolved antagonistic functions.…”
Section: Introductionmentioning
confidence: 99%